Answer:
8
Step-by-step explanation:
Pythagoras theorem I guess
Step-by-step explanation:
1/3(6+3)
= 1/3(9)
= 3
......
Answer:
C. 5
Step-by-step explanation:
Use the Distance Formula.
Substitute the values of x1 , y1 , x2 , and y2 .
|AB|² =|(1--2)²+(10-6)²|
|AB|² = |9+16|
|AB| = √ 25
|AB| =5
The correct answer of the given expression above would be the last option. We just solved this using the distributive property.
So: <span>(a - 3)(a - 5)
a^2 -3a -5a + 15
a^2 -8a + 15
Hope this is the answer that you are looking for. Have a great day!</span>